2016
DOI: 10.1016/j.autcon.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven approximation algorithms for rapid performance evaluation and optimization of civil structures

Abstract: This paper explores the use of data-driven approximation algorithms, often called surrogate modelling, in the earlystage design of structures. The use of surrogate models to rapidly evaluate design performance can lead to a more indepth exploration of a design space reduce computational time of optimization algorithms. While this approach has been widely developed and used in related disciplines such as aerospace engineering, there are few examples of its application in civil engineering. This paper focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 21 publications
(37 reference statements)
0
21
0
1
Order By: Relevance
“…A surrogate model can approximate a high-fidelity but time-consuming function in reasonable accuracy, based on sampled/labelled data obtained by design of experiments (DoE) of the high-fidelity function [15,25]. This method has been applied in building designs [13][14][15][16].…”
Section: Obtaining Performance Data For Numerous Designs By Surrogatementioning
confidence: 99%
See 4 more Smart Citations
“…A surrogate model can approximate a high-fidelity but time-consuming function in reasonable accuracy, based on sampled/labelled data obtained by design of experiments (DoE) of the high-fidelity function [15,25]. This method has been applied in building designs [13][14][15][16].…”
Section: Obtaining Performance Data For Numerous Designs By Surrogatementioning
confidence: 99%
“…Some of the methods have been used in engineering or architectural designs, including poly-nominal regression and response surface method (RSM) [16,[27][28][29], multi-layer perceptron neural network (MLPNN) [15,29] [30,31], random forest (RF) [15,32,33], radial basis function network (RBFN) [14,15], kriging [15,34,35]. In [15], these methods are used to support surrogate models for a long-span building design focusing on structural self-weight and energy. The results in [15] indicated that the MLPNN has the fastest speed and smallest errors in the data approximation of structural weight and energy consumption for the design example.…”
Section: Obtaining Performance Data For Numerous Designs By Surrogatementioning
confidence: 99%
See 3 more Smart Citations